Transformation in the transfer of Chinese accentuators by means of the Russian language - Zhao Nannan (Journal of the Belarusian State University. Philology, 2021)
Linguistic transformations used in translating accentuators from Chinese into Russian are considered. The analysis is based on the original texts of speeches by Chinese politicians and their translated Russian-language correlates. It has been established that lexical, grammatical and lexical-grammatical transformations are used when translating Chinese accentuators used in political discourse into Russian. Five types of lexical transformations have been identified: synony[1]mous translation, concretisation, generalisation, modulation (semantic development), addition. It is shown that grammati[1]cal transformations presuppose a complete or partial change in the syntactic structure and (or) morphological categories of accentuating units of the original language. Lexico-grammatical transformations undergo: elements of the ancient Chinese language Wenyan, phraseological units, collocations, neologisms. The need to use transformations of different types is explained by internal linguistic reasons (the difference in the lexical and grammatical structure of the Chinese and Russian languages), as well as by pragmatic factors (the desire for maximum accuracy in transmitting the information contained in the original text, while observing the relevant norms of the translating language). It is concluded that the presence of translation transformations is especially important in political discourse when reproducing the statements of political leaders.